2017
DOI: 10.1590/0103-8478cr20160991
|View full text |Cite
|
Sign up to set email alerts
|

Cherry tomato yield in greenhouses with different plastic covers

Abstract: The objective of the present study was to evaluate the influence of different plastic covers on microclimate and cherry tomato yield in greenhouses. The experiments were carried out in Piracicaba, state of São Paulo (Brazil), during three growing periods (2008/2009/2010). A greenhouse was divided in: Environment I (EI) - covered with plastic film anti-UV and thermo-reflective shading screen, and Environment II (EII) - covered with diffusive plastic film; monitored with automatic weather sensors; and cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Some authors have studied the infIuence of plastic covers on vegetable and fruit production. Holeman et al (2017) reported differences in cherry tomato yield in greenhouses with different plastic covers. Plastic anti-UV film and thermo-refIective shading screen showed lower fruit quantity and average fruit yield than diffusive plastic film.…”
Section: Light Infiuence In Antioxidant Activitymentioning
confidence: 99%
“…Some authors have studied the infIuence of plastic covers on vegetable and fruit production. Holeman et al (2017) reported differences in cherry tomato yield in greenhouses with different plastic covers. Plastic anti-UV film and thermo-refIective shading screen showed lower fruit quantity and average fruit yield than diffusive plastic film.…”
Section: Light Infiuence In Antioxidant Activitymentioning
confidence: 99%
“…Según Bhandari et al (2021) esto se debe a que las condiciones climáticas son un factor que afectan la calidad y rendimiento en la producción del tomate. Sin embargo, dicha situación pudiera ser manejada de mejor forma en el invernadero, favoreciendo las condiciones para el crecimiento de las plantas a través del control parcial de las variables climáticas (Holcman et al, 2017).…”
Section: Discussionunclassified
“…Holcman and Sentelhas [39] maintain that the lowest transmission of solar radiation is achieved with black polyethylene sheets ascompared with the use of red or blue sheets or with thermo-reflective sheets; the highest temperatures are reached with blue sheets.…”
Section: Othersmentioning
confidence: 99%